Le paysage façonné par le droit, entre la rationalité du droit positif et l’empirisme culturel juridique - Olivier Barrière (VertigO)
The landscape as a product of a social representation is the result of natural and human actions, a kind of alchemy socio-bio-physical in which the legal regulation intervenes heavily. Thus we can see the landscape formed by the right, especially the environmental law, the Planning right and Urbanistic law. French positive law shapes the landscape in the context of ownership, public action planning and community projects, promoting the passage of a landscape right to a right to the landscape through the principle of landscape interest.However, the codified norms and legal instruments coming from public policies are adopted and taken within a paradigm context which try to reach a heritage value of the landscape, though imperfect.By integrating into the analysis as an illustration the example of the Indians Wayana located in the context of the overseas department of French Guiana, another dimension opens up and questions arise. Participatory mapping of territorialisation conducted among satellite photographs allows a paralleling of endogenous and national regulation. This touches the sensitive point of the display of different legal paradigms, one side of the positive law, the other of a more endogenous right, resulting from specific social-cultural and economic geography.